Counterpreservation : Architectural Decay in Berlin since 1989 - Sandler, Daniela, 1974- (Book collections on Project MUSE., 2016)
"In Berlin, decrepit structures do not always denote urban blight. Decayed buildings are incorporated into everyday life as residences, exhibition spaces, shops, offices, and as leisure space. As nodes of public dialogue, they serve as platforms for dissenting views about the future and past of Berlin. In this book, Daniela Sandler introduces the concept of counterpreservation as a way to understand this intentional appropriation of decrepitude. The embrace of decay is a sign of Berlin's iconoclastic rebelliousness, but it has also been incorporated into the mainstream economy of tourism and development as part of the city's countercultural cachet. Sandler presents the possibilities and shortcomings of counterpreservation as a dynamic force in Berlpagesin and as a potential concept for other cities"--